EVALUASI PEMERIKSAAN PAJAK PENGHASILAN (PPH) DAN KEPATUHAN WAJIB PAJAK DI KANTOR PELAYANAN PAJAK (KPP) PRATAMA KENDARI - wulandari, sri; Mustakim, Mustakim; Purwati, Ninik Endang (Business UHO: Jurnal Administrasi Bisnis, 2017)
This study discusses about studying the Corporate Income Taxpayer at the Pratama Tax Office Kendari. This study used qualitative qualifications with the number of informants obtained by 8 people. This research was conducted using direct observation and interview methods.             The results of research that prove about Taxes at Kendari KPP Pratama have run quite effectively because it has reached an average of 85%. While the mandatory tax rate at KPP Pratama Kendari declined, in 2015-2016 the level of tax requirements did not reach 65% while in 2016 it increased 3% to 62%. From these results, it is expected that KPP Pratama can hold taxation knowledge dissemination, conduct more stringent tax audits and audits to increase taxpayer direction